2016
DOI: 10.1371/journal.pone.0147682
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting the mTOR Complex by Everolimus in NRAS Mutant Neuroblastoma

Abstract: High-risk neuroblastoma remains lethal in about 50% of patients despite multimodal treatment. Recent attempts to identify molecular targets for specific therapies have shown that Neuroblastoma RAS (NRAS) is significantly mutated in a small number of patients. However, few inhibitors for the potential treatment for NRAS mutant neuroblastoma have been investigated so far. In this in-vitro study, we show that MEK inhibitors AZD6244, MEK162 and PD0325901 block cell growth in NRAS mutant neuroblastoma cell lines bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
3
18
0
2
Order By: Relevance
“…Further studies of ribociclib in combination with other active agents in patients with MRT and neuroblastoma are ongoing, such as the AcS e-ESMART multi-arm trial (NCT02813135), which includes ribociclib in combination with everolimus (a PI3K/ AKT/mTOR pathway inhibitor) or chemotherapy in patients prescreened for specific molecular alterations. The combination with everolimus was based on the observation that the PI3K/AKT/ mTOR pathway, for example, via MYCN, ALK, or RAS activation, may be implicated in the pathogenesis of neuroblastoma and MRT (30,31). Other ribociclib-based combinations with other targeted therapies, such as MAPK/ERK inhibitors, may be considered in future trials.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies of ribociclib in combination with other active agents in patients with MRT and neuroblastoma are ongoing, such as the AcS e-ESMART multi-arm trial (NCT02813135), which includes ribociclib in combination with everolimus (a PI3K/ AKT/mTOR pathway inhibitor) or chemotherapy in patients prescreened for specific molecular alterations. The combination with everolimus was based on the observation that the PI3K/AKT/ mTOR pathway, for example, via MYCN, ALK, or RAS activation, may be implicated in the pathogenesis of neuroblastoma and MRT (30,31). Other ribociclib-based combinations with other targeted therapies, such as MAPK/ERK inhibitors, may be considered in future trials.…”
Section: Discussionmentioning
confidence: 99%
“…(5, 6) Although single agent activity was modest in some preclinical studies,(7, 8) data suggest that mTOR inhibitors may be effective in subsets of neuroblastoma tumours. (9) In addition, mTOR inhibitors have synergistic or additive effects when combined with chemotherapeutics. (10, 11) Previous studies provided temsirolimus dosing information,(12, 13) and a COG trial demonstrated that I/T/TEM could be delivered safely to children with relapsed/refractory solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Необходимо продолжить изучение биологии опухоли и на основании этого индивидуализировать подход к лечению. Возможно использование различных видов таргетных препаратов [23][24][25] и иммунотерапии (различных опухолеспецифических антител, CAR-T-клеток, ДНК и белковых вакцин) станет лучшим видом лечения для данной категории пациентов [26,27]. Проведение исследований в этой области требует объединения усилий специалистов разных стран и исследовательских центров.…”
Section: обсуждение основного результата исследованияunclassified